Frameworks of the maturity model for Industry 4.0 with assessment of maturity levels on the example of the segment of steel enterprises in Poland - Bożena Gajdzik (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The aim of the article is to present the author's concept of steel market enterprises' maturity for functioning in Industry 4.0. The model is based on the assessment of key technologies or pillars of the new industrial concept. The proposed assessment includes five levels of investment maturity under the conditions of the fourth industrial revolution (a five-point assessment scale was used to measure the degree of maturity of developed enterprises by implemented projects of smart manufacturing (SM). The maturity assessment proposal is based on direct research. The research was carried out in the segment of enterprises from the Polish steel sector. The tool used for the research was a questionnaire survey. The research was carried out with 79 selected steel enterprises in Poland for the pilot study. On the basis of the research, it was established that the segment of enterprises in the Polish steel market are at the third level of maturity in the five-level scale of the model, where level 1 is the 'preliminary' level, and 5 represents the optimal maturity level. Within particular pillars of Industry 4.0, according to all respondents, the biggest changes in terms of implementing the industrial concept took place in connection with the use of Internet and mobile technologies in the process of customer service, including EDI, an e-invoicing system. The second position belonged to investments in production automation with the use of individual machines (installation of sensors on devices and sensors for collecting data on the state of the machine). In addition, similar and relatively higher answers were given by respondents to questions about the development and compatibility of IT systems for production support, such as CAx, MRP, MES. The remaining technological pillars, such as data processing from machines, installations of real-time data; network and chain integration (end -to -end engineering); production automation with the use of interoperating machines (production nests); expansion of databases (Big Data) and visualisation of processes together with their optimisation using IoT were found to be initiated as activities in very large and large enterprises. The lowest rated scope of investment changes concerned the block chain in the steel sector. The research of investment of enterprises can be used to assess the maturity of enterprises in this segment of industry in Poland.
Keywords: 650; Industry 4.0 (I 4.0); maturity model (MM); smart manufacturing (SM); steel industry